Influence of the Surrounding Plants by Rapeseed Field on Population Density of Cabbage Aphid (Brevicoryne brassicae L.) and its Biological Enemies - Baghdad Science Journal (مجلة بغداد للعلوم)
The result revealed that the peak of population density of cabbage aphid Brevicoryne brassicae was 523.20 individuals/plant on 21 March in edges of rapeseed field and was 1141.67 individuals/plant in center of the field. Results revealed that population density of cabbage aphid in rapeseed fields surrounded by cover crops significantly were low compared with that of monoculture rapeseed. The location of rapeseed plants (in edges or in center) significantly affected (p